Il cardinale Pietro Gasparri, segretario di Stato (1914-1930) - Pettinaroli, Laura; Valente, Massimiliano (Online-Schriften des DHI Rom. Neue Reihe | Pubblicazioni online del DHI Roma. Nuova serie, 2020)
Pietro Gasparri (1852-1934) was a famous jurist, a valued university professor and an able papal diplomat. He headed the Secretary of State and the Roman Curia from November 1914 to January 1930, during a crucial period in the history of Europe and of the Papacy. This book - the outcome of research seminars on "The international policy of the Holy See" held in Rome between 2013 and 2016 in collaboration with the Università europea di Roma and the Institut catholique de Paris - gathers the contributions of an international group of historians and archivists, seniors and PhD students. It focuses on Gasparri in his role as Secretary of State: a central figure of the government of the Church in the twentieth century